Blockchain technology and gender equality: A systematic literature review. (February 2023) - Di Vaio, Assunta; Hassan, Rohail; Palladino, Rosa
Abstract: This study examines the literary corpus on the role and potential of blockchain technology in promoting gender equality through the lens of new technology-oriented corporate governance models. It investigates if and how corporate governance models can include blockchain technology to add value to gender equality and inclusion processes, in line with Sustainable Development Goal (SDG) 5. A bibliometric analysis of a database—containing 127 articles, 4 United Nations reports, 3 European institutions' reports, 1 International Labour Office report, 1 World Economic Forum report, and 4 industry reports useful to our analysis—was conducted from 1990 to 2021, to provide a map of the knowledge generated and circulated by the literature. This study offers insights into publication activities, essential topics, citation trends, and the status of collaborations between contributors to previous research and aggregated contributions to the area of blockchain technology studies. Furthermore, the study offers a retrospective analysis of the content published in the blockchain technology field. The findings indicate that field research has focussed primarily on blockchain's economic and financial attributes but not on social potential. This study emphasises the implementation of blockchain technology to manage gender equality and inclusion processes by orienting corporate governance models towards social and sustainable values. Highlights: Blockchain Technology (BT) encourages gender equality and inclusion processes. BT performs well in technology-oriented corporate governance models. BT favours the achievement of SDG#5. BT can address the digital gender gap. BT needs mentoring programmes and female leadership in corporate governance models.